2022
DOI: 10.1007/s10549-021-06445-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of personalized screening and prevention recommendations in the general population through breast cancer risk assessment: results from a dedicated risk clinic

Abstract: Purpose A personalized approach to prevention and early detection based on known risk factors should contribute to early diagnosis and treatment of breast cancer. We initiated a risk assessment clinic for all women wishing to undergo an individual breast cancer risk assessment. Methods Women underwent a complete breast cancer assessment including a questionnaire, mammogram with evaluation of breast density, collection of saliva sample, consultation with a radiologist, and a breast cancer specialist. Women aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…For the same threshold, the integrated model reclassified 15% of UK women (5% from above to below and 10% in the opposite direction), identifying an additional 16% of the future cases. Saghatchian et al [ 51 ] reported the feasibility of giving screening recommendations based on individual risk in the general population. The use of PRS changed the risk score and monitoring and prevention recommendations in 40% of women, 28% of which classified from intermediate to moderate or high risk.…”
Section: Discussionmentioning
confidence: 99%
“…For the same threshold, the integrated model reclassified 15% of UK women (5% from above to below and 10% in the opposite direction), identifying an additional 16% of the future cases. Saghatchian et al [ 51 ] reported the feasibility of giving screening recommendations based on individual risk in the general population. The use of PRS changed the risk score and monitoring and prevention recommendations in 40% of women, 28% of which classified from intermediate to moderate or high risk.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review published in July 2022 [69] also emphasised that there are currently no endorsed risk prediction models for breast cancer tailored to diverse ethnic populations. Furthermore, we did not assess a machine learningbased software tool, the Mammo-Risk ™ model (Predilife, Villejuif, France) [70], as it was published in 2022. Te model was developed in the BCSC cohort [71,72] to estimate the risk of developing breast cancer within the next fve years based on the following four risk factors: age, family history of breast cancer, history of breast biopsies, and breast density with or without a polygenic risk score.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 presents an overview of the discriminatory accuracy of the identifed empirical and genetic breast cancer risk prediction models and shows that almost all identifed model versions had a limited discriminatory accuracy with AUC values <0. 70 One study did not report on the population. Te discriminatory accuracy of these original models ranged from AUC values of 0.53 [38] to 0.785 [45], whereby the latter applied to the prediction of ER-positive, HER2negative, invasive, and noninvasive carcinoma in a Japanese population considering a polygenic risk score.…”
Section: Both Studies Included Caucasian Populationsmentioning
confidence: 99%
“…The lifestyle/familial-expanded AI risk model showed an advantage over the imaging-only AI risk model for identifying ER-positive breast cancers across the 1–10-year follow-up. Women therefore could have an advantage in having their risk assessed using the lifestyle/familial-expanded model when considering prophylactic endocrine therapy to reduce their risk of developing breast cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%